BNIP3L-dependent mitophagy accounts for mitochondrial clearance during 3 factors-induced somatic cell reprogramming. Issue 9 (2nd September 2017) - Xiang, Ge; Yang, Liang; Long, Qi; Chen, Keshi; Tang, Haite; Wu, Yi; Liu, Zihuang; Zhou, Yanshuang; Qi, Juntao; Zheng, Lingjun; Liu, Wenbo; Ying, Zhongfu; et al.
ABSTRACT: Induced pluripotent stem cells (iPSCs) have fewer and immature mitochondria than somatic cells and mainly rely on glycolysis for energy source. During somatic cell reprogramming, somatic mitochondria and other organelles get remodeled. However, events of organelle remodeling and interaction during somatic cell reprogramming have not been extensively explored. We show that both SKP/SKO ( Sox2, Klf4, Pou5f1 / Oct4 ) and SKPM/SKOM (SKP/SKO plus Myc / c-Myc ) reprogramming lead to decreased mitochondrial mass but with different kinetics and by divergent pathways. Rapid, MYC/c-MYC-induced cell proliferation may function as the main driver of mitochondrial decrease in SKPM/SKOM reprogramming. In SKP/SKO reprogramming, however, mitochondrial mass initially increases and subsequently decreases via mitophagy. This mitophagy is dependent on the mitochondrial outer membrane receptor BNIP3L/NIX but not on mitochondrial membrane potential (ΔΨm ) dissipation, and this SKP/SKO-induced mitophagy functions in an important role during the reprogramming process. Furthermore, endosome-related RAB5 is involved in mitophagosome formation in SKP/SKO reprogramming. These results reveal a novel role of mitophagy in reprogramming that entails the interaction between mitochondria, macroautophagy/autophagy and endosomes.